Electrical, structural and optical properties of Cd1-xZnxTe thick polycrystalline films. (March 2018) - Znamenshchykov, Y.V.; Kosyak, V.V.; Kononov, O.K.; Shpetnyi, I.O.; Grebinaha, V.I.; Fochuk, P.M.; Opanasyuk, A.S.
Abstract: Thick polycrystalline Cd1- x Zn x Te films with different Zn concentration were deposited by the close-spaced vacuum sublimation method on ITO-coated glass substrates. In order to evaluate the usefulness of the films as a base layer in X-ray detector, the study of their electrical properties and photoresponse was carried out. Structural, microstructural properties and phase composition of the films were investigated using X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, and Raman spectroscopy. It was found that films have cubic zinc-blende crystal lattice; the microstructural analysis showed that crystalline quality (e.g. coherent scattering domains size and microstrains level) of the films is decreasing with increasing of Zn concentration. Raman measurements showed only CdTe- and ZnTe-related vibrational modes, which indicates the absence of tellurium inclusions at the surface. The temporal photoresponse of the detector was described with the help of the analytical model, taking into account the presence of two types of recombination centers. As a result, the parameters of the recombination centers and their possible influence on the current flow in the films were established. Highlights: Cd1-x Znx Te thick films on ITO-coated glass substrates were studied. Effect of metals content on samples structural properties was investigated. The IV dependencies and photoresponse of the Au/Cd1-x Znx Te samples were analyzed. The model of photocurrent relaxation with the participation of carrier's traps was proposed.